Characterization of bottom sediments in the Río de la Plata estuary - Moreira, Diego (2015)
Bottom sediments and surface water samples were collected in the intermediate and outer Río de la Plata (RDP) estuary, South America, during 2009?10, in six repeated cruises, with 26 stations each. Samples were processed for grain size and for water and organic matter content. The aim of this work is to analyze this new data set to provide a comprehensive and objective characterization of the bottom sediment distribution, to study the composition, and to construct a conceptual model of the involved physical mechanisms. Principal components analysis is applied to the bottom sediment size histograms to investigate the spatial patterns. Variations in grain size parameters contain information on possible sediment transport patterns, which were analyzed by means of trend vectors. Sediments show a gradational arrangement of textures: sand dominant at the head, silt in the intermediate estuary, and clayey silt and clay at its mouth. Textures become progressively more poorly sorted offshore, and the water and organic matter content increase and seem to be strongly related to the geometry and the hydrodynamics. Along the northern coast of the intermediate RDP, well-sorted medium and fine silt predominates, whereas along the southern coast, coarser and less sorted silt prevails from differences in tidal currents, in the tributaries´ water pathways, or both. Around Barra del Indio, clay prevails over silt and sand, and the water and organic matter content reach a maximum, probably because of flocculation and reduction of the currents. Immediately seaward of the bottom salinity front, net transport reverses its direction, and well-sorted, coarser sand from the adjacent shelf dominates. Relict sediment is observed between the Santa Lucía River and Montevideo, consisting of poorly sorted fine silt and clay. The inferred net transport suggests convergence at the bottom salinity front, where the limit of the estuarine deposits is observed.